Evaluation of the P-Delta Effect on Collapse Capacity of Adjacent Structures Subjected to Far-field Ground Motions - Farzin Kazemi; Benyamin Mohebi; Mansoor Yakhchalian (Salehan Institute of Higher Education, 2018)
In urban areas, adjacent structures can be seen in any insufficient distance from each other, because of economic reasons and refusal of acquired minimum separation distance according to seismic previsions. Collapse capacity assessment of structures is one of the important objectives of performance-based seismic engineering. The purpose of this study is to consider the pounding phenomenon and P-Delta effect in seismic collapse capacity assessment of structures. For this purpose, 2-, 4-, 6- and 8-story adjacent structures with different conditions of separation distance among them, were modeled in the OpenSees software. Furthermore, Incremental Dynamic Analyses (IDAs) were performed using 78 far-field ground motion records to compute the collapse capacities of adjacent structures. The results obtained from IDAs for adjacent structures show that during pounding, taller structure reaches its collapse capacity earlier than shorter one. In addition, by considering the P-Delta effect and increasing the distance between adjacent structures, time of collapse and number of impacts increases. According to results, considering the P-Delta effect in modeling has significant influence in seismic collapse capacity assessment of pounding structures.